Dissecting transcriptomic signatures of neuronal differentiation and maturation using iPSCs - Emily E. Burke (Nature Portfolio, 2020)
Here, authors present results of a hiPSC transcriptomics study on corticogenesis from multiple donors across four transitions in differentiation. They present a bulk data deconvolution method and show that co-culturing human NPCs with rodent astrocytes results in mutually synergistic maturation.